Identifying and Coding Behavioral Indicators of Social Presence With a Social Presence Behavioral Coding System - Hayes, Aleshia Taylor; Hughes, Charles E.; Bailenson, Jeremy (Frontiers in Virtual Reality, 2022)
Social presence, the sense of connection with another, is more important than ever as teachers, healthcare providers, and other professionals are using immersive tools to facilitate the social interaction for education, training, therapy and collaboration between geographically distributed humans and surrogates (avatars, agents, or robots). Leading researchers cite the subjective nature of the traditional self-report measures of social presence and the absence of a standardized approach to measuring social presence as a constraint to gaining deeper understanding of user’s experiences of emerging and existing tools. This discourse highlights behavioral indicators of social presence that have been identified over decades across disciplines from psychology, communication, computer science, education, and engineering. The authors explicate the behavioral themes of social presence and describe a classification system grounded in exogenic and endogenic themes of social presence. This article goes on to describe the design of a social presence behavioral coding system (SPBCS) instrument that provides a structure to coding behaviors associated with a users’ experience of social presence. The behavioral coding system described in this paper is the first step in creating a robust standardized approach to quantifying social presence through behavioral, physiological, and subjective indicators that ultimately may replace the current standard subjective approaches to describing the user’s experience in all realities.